Camouflage of Severe Skeletal Class II Gummy Smile Patient Treated Nonsurgically with Mini Implants - Qamruddin, Irfan; Shahid, Fazal; Alam, Mohammad Khursheed; Jamal, Wafa Zehra (Hindawi Publishing Corporation, 2014)
Skeletal class II has always been a challenge in orthodontics and often needs assistance of surgical orthodontics in nongrowing patients when it presents with severe discrepancy. Difficulty increases more when vertical dysplasia is also associated with sagittal discrepancy. The advent of mini implants in orthodontics has broadened the spectrum of camouflage treatment. This case report presents a 16-year-old nongrowing girl with severe class II because of retrognathic mandible, and anterior dentoalveolar protrusion sagittally and vertically resulted in severe overjet of 13mmand excessive display of incisors and gums. Bothmaxillary central incisors were trimmed by general practitioner few years back to reduce visibility. Treatment involved use of micro implant for retraction and intrusion of anterior maxillary dentoalveolar segment while lower incisors were proclined to obtain normal overjet, and overbite and pleasing soft tissue profile. Smile esthetics was further improved with composite restoration of incisal edges of both central incisors.